Ethnicity and globalization : from migrant worker to transnational citizen - Castles, Stephen (London ; Thousand Oaks, Calif. : Sage Publications, 2000)
"Using techniques of comparative analysis, the book demonstrates the lag between global migration and policy. As the postwar demand for labour outstripped supply, immigration of workers of various ethnic and social backgrounds was encouraged throughout the developed West. However, the implantation of new ethnicities in different soils was neither planned nor managed effectively. The later chapters go on to show how globalization and the emergence of transnational networks have transformed migration since the 1980s, giving rise to complex flows of labour migrants, refugees, asylum seekers, highly-skilled personnel and settlers." "Ethnicity and Globalization will be for anyone interested in debates on migration, citizenship and globalization."--Jacket.
Thirty Years of Research on Migration and Multicultural Societies -- The Function of Labour Migration in Western European Capitalism -- The Social Time Bomb : Education of an Underclass in West Germany -- The Guest-worker in Western Europe : an Obituary -- Migration and Minorities in Europe : Perspectives for the 1990s -- Eleven Hypotheses -- Contract Labour Migration -- Migration in the Asian Pacific Region: Before and After the Crisis -- Globalization and Migration : Some Pressing Contradictions -- Multicultural Citizenship : the Australian Experience -- Explaining Racism in the New Germany -- The Racisms of Globalization -- Citizenship and the Other in the Age of Migration -- Postscript : the Next Thirty Years.
Includes bibliographical references (pages 208-219) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Emigration and immigration; Ethnicity; Globalization; Multiculturalism; International relations; Emigration and Immigration; Émigration et immigration; Ethnicité.; Relations internationales; Mondialisation; Multiculturalisme; ethnicity; globalism; multiculturalism; international relations; emigration; Migration period (Medieval culture or period); immigration; migrations (events); SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; Emigration and immigration; Ethnicity; Globalization; International relations; Multiculturalism; Ethnische Identität; Ethnizität; Globalisierung; Internationale Migration; Multikulturelle Gesellschaft; Migratie (demografie); Etnisch bewustzijn; Internationalisatie; international migration; migrant workers; migration policy; ethnic group; globalization; trend; cultural change; human rights; social integration; racial discrimination; developed countries; developing countries; Emigration and immigration; Ethnicity; Globalization; Multiculturalism; migration internationale; travailleur migrant; politique migratoire; groupe ethnique; mondialisation; tendance; changement culturel; droits de l'homme.